Usage Policies for Decentralised Information Processing - Speiser, Sebastian (KIT Scientific Publishing, 2013)
Owners impose usage restrictions on their information, which can be based e.g. on privacy laws, copyright law or social conventions. Often, information is processed in complex constellations without central control. In this work, we introduce technologies to formally express usage restrictions in a machine-interpretable way as so-called policies that enable the creation of decentralised systems that provide, consume and process distributed information in compliance with their usage restrictions.